2015
DOI: 10.1111/gcb.12830
|View full text |Cite
|
Sign up to set email alerts
|

Response of wheat growth, grain yield and water use to elevated CO2 under a Free‐Air CO2 Enrichment (FACE) experiment and modelling in a semi‐arid environment

Abstract: The response of wheat crops to elevated CO 2 (eCO 2) was measured and modelled with the Australian Grains Free‐Air CO 2 Enrichment experiment, located at Horsham, Australia. Treatments included CO 2 by water, N and temperature. The location represents a semi‐arid environment with a seasonal VPD of around 0.5 kPa. Over 3 years, the observed mean biomass at anthesis and grain yield ranged from 4200 to 10 200 kg ha−1 and 1600 to 3900 kg ha−1, respectively, over various sowing times and irrigation regimes. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(113 citation statements)
references
References 86 publications
(126 reference statements)
12
96
2
Order By: Relevance
“…An average grain-yield increase of 15% in bread wheat grown at elevated CO 2 in FACE experiments has been found through meta-analyses (Ainsworth and Long 2005). Increases of 10% and of 26% have been reported in German and Australian environments, respectively (Högy et al 2010;O'Leary et al 2015). The first conclusion is therefore a confirmation of the 'fertiliser' role of elevated CO 2 even in winter wheat in the Southern European environment considered here.…”
supporting
confidence: 71%
“…An average grain-yield increase of 15% in bread wheat grown at elevated CO 2 in FACE experiments has been found through meta-analyses (Ainsworth and Long 2005). Increases of 10% and of 26% have been reported in German and Australian environments, respectively (Högy et al 2010;O'Leary et al 2015). The first conclusion is therefore a confirmation of the 'fertiliser' role of elevated CO 2 even in winter wheat in the Southern European environment considered here.…”
supporting
confidence: 71%
“…These simulations were performed using CropSyst (Stockle et al, 1994;Stöckle et al, 2003), a cropping system model that has been widely used for climate change assessment studies under different climatic conditions around the world (Sommer et al, 2013;Donatelli et al, 2015;Holzkämper et al, 2015;O'Leary et al, 2015). Downscaled gridded daily weather data (4 × 4 km) for the period 1979-2010 (Abatzoglou, 2013) were used for baseline simulations.…”
Section: Crop Yield Simulationsmentioning
confidence: 99%
“…These projections remained unchanged when the variation of downloaded weather from 12 GCMs used in this study was considered or when yields with a probability of exceedance of 70% were used to classify AECs. One weakness of the study is the use of a single crop model for yield projections, although the CropSyst model has been used extensively in wheat studies in the IPNW (Pannkuk et al, 1998;Peralta and Stöckle, 2002;Stöckle et al, 2010; and around the world, Pala et al, 1996;Sommer et al, 2013;Donatelli et al, 2015;Holzkämper et al, 2015;O'Leary et al, 2015). Previous studies conducted with other models have also shown positive impacts of climate change in the region (Thomson et al, 2002;Rosenzweig and Tubiello, 2007).…”
Section: Aec Classification Based On Yield Percentilesmentioning
confidence: 99%
“…Inclusion of CO 2 fertilization in crop models leads to projected increases in wheat yields for the Pacific Northwest of the USA well into the 21st century despite the negative effects of warming [66,96]. The yield gain measured in the Free-Air CO 2 Enrichment (FACE) experiment at 550 ppm (representing expected concentrations for 2050) at Horsham, Australia, was 25% and so exceeds the national projected losses to that date in the absence of fertilization (12%) [97]. However, FACE experiments also have limitations because they measure response to CO 2 without the temperature, precipitation, and vapour pressure differences of future climates.…”
Section: Addressing the Challengesmentioning
confidence: 98%